Injury profile of employees at a specific beverage manufacturing company: a retrospective study - L. Chetty; J. Jelsma; S. Maart (AOSIS, 2007)
This article reports on important information pertaining to the prevalence of occupational injuries. At present very little data existson the prevalence of occupational injuries in South Africa.  A retrospective study was undertaken to detail the occupational injuries sustained by employees at a specific beverage manufacturing company. The aim of this study was to determine the mechanisms, type, classification, anatomical site, frequency and time of injuries at this beverage company. The sample consisted of all employees that reported to the occupational health clinic with occupational injuries during the six-month review period i.e. July 2004-December 2004. Results of this review were computed in a self-complied injury data spreadsheet. The data was presented descriptively and the level of significance was set at 0.05.  Incorrect lifting of manual materials was reported as the most common mechanism of injury. Repetitive strain injuries were the most common type of injury. The spine/trunk was the site of 48 (66.7% of regions) injuries with the most frequently injured regions being the back (43.1%) and neck (22.2%). Most of the injuries were sustained during the month of December (27.8%). It is recommended that aggressive health promotion and injury prevention strategies be implemented to reduce the burden of occupational injuries at this specific beverage manufacturing company.